An analysis of the errors in the calculation of ice discharge through flux gates. Application to Nunavut tidewater glaciers, Canada - Sánchez Gámez, Pablo; Navarro Valero, Francisco José (E.T.S.I. Telecomunicación (UPM), 2018)
Five 20-m deep firn cores were extracted and analyzed for density and stratigraphy, two full energy balance weather stations were deployed, equipped with 16 m long thermistor strings to measure firn temperature, and over 300 km of ground penetrating radar data were collected. Preliminary firn cores analysis reveals increasing frequency and thickness of ice lenses toward lower ice-sheet elevations, in agreement with other recent work in the area. The collected data will facilitate advances in our understanding of the spatio-temporal distribution and variability of firn refreezing and its role in the surface mass balance of the Greenland Ice Sheet.